Drosofilídeos e seus himenópteros parasitoides em coffea arabica L - Fernandes, Daniell Rodrigo Rodrigues [UNESP]; Lara, Rogéria Inês Rosa; Perioto, Nelson Wanderley (My University, 2009)
The objective of this study was to evaluate the occurrence of Drosophilidae and their parasitoids in coffee fruits in Cravinhos, SP, Brazil. The fruits were collected directly from the tree, and a portion was exposed under the canopy. Fifty-nine drosophilid pupae were collected in all, of which 31 adults (including two Ganaspis exemplars) emerged. The survival rate of all pupae was 49.2%. Thirty-five drosopholid pupae were obtained from the fruit trees, 24 of which later emerged, three different species: Zaprionus indianus Gupta, Drosophila nebulosa Sturtevant and D. simulans Sturtevant. From the fruits under the canopy of plants were obtained 24 pupae of four different species: Z. indianus, D. cardini Sturtevant, D. immigrans Sturtevant and D. willistoni Sturtevant. The emergence of two Ganaspis sp. (Hymenoptera: Figitidae) examples, with a parasitism rate of 8.3%, was also observed. Half of the drosophilids collected are introduced species and represented 79% of the adults emerged. Associations between Z. indianus, D. cardini, D. immigrans, D. nebulosa, D. simulans and D. willistoni and the coffee crop are reported herein.
Drosophilidae and their parasitic hymenoptera in a coffea arabica L. crop
Keywords: Coffea arabica; Drosophila spp.; Fig fly; Figitidae; Ganaspis sp.; Zaprionus indianus; Drosophila cardini; Drosophila immigrans; Drosophila nebulosa; Drosophila simulans; Drosophila willistoni; Drosophilidae; Ganaspis; Hymenoptera